Предмет: Алгебра,
автор: dyuzbaevaalina
(tg+ctg)^2-(tg-ctg)^2=4 доказать
Ответы
Автор ответа:
0
(tg+ctg)²-(tg-ctg)²=4
tg²+2tg*ctgx+ctg²-(tg²-2tg*ctg+ctg²)=4
tg²+2tg*ctg+ctg²-tg²+2tg*ctg-ctg²=4
4tg*ctg=4
(sin/cos)*(cos/sin)=1
1=1
tg²+2tg*ctgx+ctg²-(tg²-2tg*ctg+ctg²)=4
tg²+2tg*ctg+ctg²-tg²+2tg*ctg-ctg²=4
4tg*ctg=4
(sin/cos)*(cos/sin)=1
1=1
Похожие вопросы
Предмет: Математика,
автор: Adelya594
Предмет: Алгебра,
автор: Аноним
Предмет: Английский язык,
автор: anastasimedvedeva23
Предмет: Алгебра,
автор: kapkaev98